Home-based vs center-based exercise on patient-reported and performance-based outcomes for knee osteoarthritis: a systematic review with meta-analysis - Zhang, Zhi-Yuan; Huang, Lu; Tian, Lv; Yi, Jiang; Gao, Min; Wang, Xiao-Qi; Jiang, Jun-Jie; Liu, Zhong-Liang (Frontiers in Public Health, 2024)
Background Home-based exercise (HBE) represents an alternative to increase the accessibility of rehabilitation programs and relieve the burden on the health care system for people with knee osteoarthritis. Objectives To summarize for the first time the effectiveness of HBE as compared to center-based exercise (CBE), both with and without HBE, on patient-reported and performance-based outcomes in people with KOA. Methods Searches were conducted on PubMed, Cochrane, Embase, Web of Science, and Scopus until March 10, 2023, without date or language restrictions. Randomized controlled trials investigating HBE versus CBE or HBE combined with CBE for people with KOA were eligible. The primary outcomes were patient-reported: pain, physical disability, and quality of life. The secondary outcomes were performance-based: walking ability, lower limb muscle strength, and balance function. Risk of bias was assessed with the Cochrane Risk of Bias tool and quality of evidence according to the GRADE. Results Eleven trials involving 956 participants were included. There was no difference in short-term pain (SMD, 0.22 [95% CI, −0.04 to 0.47], p = 0.09; I2 = 0%), physical disability (SMD, 0.17 [95% CI, −0.19 to 0.54], p = 0.35; I2 = 0%), walking ability (SMD, −0.21 [95% CI, −0.64 to 0.22], p = 0.33; I2 = 35%) and lower limb muscle strength (SMD, −0.24 [95% CI, −0.88 to 0.41], p = 0.47; I2 = 69%) between HBE and CBE. HBE combined with CBE has better benefits compared with HBE alone in short-term pain (SMD, 0.89 [95% CI, 0.60 to 1.17], p < 0.001; I2 = 11%) and physical disability (SMD, 0.25 [95% CI, 0.00 to 0.50], p = 0.05; I2 = 0%). Conclusion Based on limited evidence, HBE is as effective as CBE on short-term pain, physical disability, walking ability, and lower limb muscle strength in people with knee osteoarthritis. Furthermore, combining HBE with CBE may enhance the overall efficacy of the intervention. Systematic review registration PROSPERO, CRD42023416548.